ANALISIS KONFLIK BATIN TOKOH UTAMA DAN NILAI PENDIDIKAN KARAKTER NOVELET KETIKA MAS GAGAH PERGI KARYA HELVY TIANA ROSA SERTA RELEVANSINYA SEBAGAI BAHAN AJAR SASTRA DI SMA - Widowati, Rahmadhani Briliannisa; Wardani, Nugraheni Eko; Mulyono, Slamet (Universitas Sebelas Maret, 2018)
This form of research is descriptive qualitative research. The data sources of this research are novel and informants. Technique of taking research subject is purposive sampling. Data collection techniques used is technique read dan write dan interviews. Test the validity of data using triangulation of data sources and theory. Data analysis technique used is flow analysis technique. The result show that: (1) the theme raised in the novelet is the deity, the protagonist, the plot is a forward flow, the story set in Jakarta in 1994, the point of view of the first person the main character, his message is to be a good agent of Goodness; (2) Gagah and Yudi characters have elements id, ego, and superego, Gita character has high id and ego and experiencing the most powerful inner conflicts; (3) the value of character education contained in the novelet includes religious, honest, tolerant, disciplined, creative, independent, democratic, curiosity, friendly/communicative, peace loving, reading, caring, caring, responsible; and (4) the novelet Ketika Mas Gagah Pergi is relevant to be used as a teaching material when viewed from its relation with instructional objectives to be achieved, also from the aspect of content, presentation, language, and graph.